Українські та російські дослідники людського потенціалу у XVII-XX століттях - Яковенко, Р. В.; Yakovenko, R. (София : „Бял ГРАД-БГ” ООД, 2010)
Досліджено ключові відмінності між положеннями російських та українських дослідників людського потенціалу в царині політичної економії The key differences between the provisions of Russian and Ukrainian researchers of human potential in the field of political economy are investigated
Ukrainian and Russian researchers of human potential in the 17th-20th centuries
Keywords: робоча сила; людський потенціал; продуктивні сили; добробут; бідність; капіталізм; labour force; human potential; means of production; well-being; poverty; capitalism